2019
DOI: 10.1186/s12978-019-0837-z
|View full text |Cite
|
Sign up to set email alerts
|

Understanding mistreatment during institutional delivery in Northeast Nigeria: a mixed-method study

Abstract: BackgroundImproving quality of care including the clinical aspects and the experience of care has been advocated for improved coverage and better childbirth outcomes.ObjectiveThis study aimed to explore the quality of care relating to the prevalence and manifestations of mistreatment during institutional birth in Gombe State, northeast Nigeria, an area of low institutional delivery coverage.MethodsThe frequency of dimensions of mistreatment experienced by women delivering in 10 health facilities of Gombe State… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 55 publications
1
21
0
Order By: Relevance
“…Our findings are consistent with studies from Ethiopia, Ghana, Kenya, Nigeria and the Philippines which have reported a strong association between improvements in structural quality and the availability of commodities with a substantial increase in health facility utilisation 53 54. Interestingly, the utility associated with drug and supply constraints was negative but did not reach statistical significance, perhaps a reflection of women in Gombe having coping strategies for persistent shortages of drugs and supply by sourcing these outside of the health system, rather than an indication of not caring about drugs and supply constraints 15…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our findings are consistent with studies from Ethiopia, Ghana, Kenya, Nigeria and the Philippines which have reported a strong association between improvements in structural quality and the availability of commodities with a substantial increase in health facility utilisation 53 54. Interestingly, the utility associated with drug and supply constraints was negative but did not reach statistical significance, perhaps a reflection of women in Gombe having coping strategies for persistent shortages of drugs and supply by sourcing these outside of the health system, rather than an indication of not caring about drugs and supply constraints 15…”
Section: Discussionmentioning
confidence: 99%
“…These negative experiences during facility-based birth have been found to undermine women’s trust in the health system, and negatively impacted their subsequent decision to deliver in the health facility 56–58. In an earlier study in Gombe State, only 3% of women reported mistreatment related to physical abuse, and less than 1% reported mistreatment related to sexual abuse during labour and delivery 15. Nonetheless, we found that absence of physical abuse and absence of sexual abuse influenced women’s hypothetical choice for place of delivery.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations